(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Savchenko L. О. The analysis of normative documents as for improving education of future technology teachers and draft through pedagogical diagnostics facilities The article analyzes curricula, educational standards of training future technology and drawing teacher for pedagogical diagnostics of quality of education. Considerable changes towards training a future teacher have been recently observed, but little attention has been paid to training a future technology teacher for pedagogical diagnostics in the process of studying special disciplines.